The Effect of some Coordination Abilities on Developing kinematical Motor behavior and the Accuracy of Jump Spike Serve in volleyball players - Yasir , Alaa Muhsun (International Journal of Psychosocial Rehabilitation, 2020)
The intentional sample of the research consisted of Baghdad University volleyball team players (volleyball (2019-2020), whose number was (12) players. The researcher used special exercises according to coordination abilities (sense-kinetics) to develop kinematic motor behavior and the accuracy of the jump spike serve skill, as the analysis program was used( Kinovea) in order to extract the kinematic variables of the jump spike serve skill.The jump spike serve skill accuracy test was used for volleyball players in three regions. The aim of the study was to identify the effect of coordination abilities exercises (kinetic motor) on the kinematic variables (kinematic behavior) and the accuracy of jump spike serve skill of the University of Baghdad players in volleyball. The individuals of the sample were characterized by the performance of the jump spike serve skill with the highest accuracy. The mechanical variables (such as motor mechanical kinetic behavior) improved as a result of the effect of coordination exercises (sense-kinetics).